Pengaruh Green Marketing, Sosial Media Marketing, Dan Promosi Terhadap Keputusan Pembelian Pada Mekar Swalayan Kediri - Erlia Novita Sari; Deby Santyo Rusandy; Anita Sumelvia Dewi (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
This research discuesses the loss of Green Marketing, Social Media Marketing, and Promotion of Purchase Decisions in Mekar Swalayan Kediri. this research aims to find out the result of the influence of green marketing, sosial media marketing, and promotion on purchasing decisions in Mekar Swalayan Kediri. the method in this research in quantitative. Data collection techniques using primary data and secondary data. Sampling in this study using purposive sampling teachnique with 99 customers. Data processing uses validity test, reliability test, classic assumption test, multiple linear regression, t test, F test, and the coefficient of determination (R2). There is a partial effect between Green Marketing on Purchase Decision where the results of the t test obtained a significant value of 0,009 < 0,05. There is a partial effect between Social Media Marketing on Purchase Decision where the results of the t test show a significance value of 0,011 < 0,05. There is a partial effect between Promotion on Purchase Decision wehere the results of the t test obtained a significance value of 0,002 < 0,05. There is a simultaneous effect of Green Marketing, Social Media Marketing, and Promotion on Purchase Decision where the results of the F test get a significance value of 0,000 < 0,05.